Safety netting advice for acutely ill children presenting to ambulatory care: exploring parents’ opinions, ideas, and expectations through focus group interviews - Ruben Burvenich; Stefan Heytens; David A.G. Bos; Kaatje Van Roy; Thomas Struyf; Jaan Toelen; An De Sutter; Jan Y. Verbakel (BMC Primary Care)
Abstract Background Safety netting advice (SNA) is an essential component of the management of acutely ill children in ambulatory care. However, healthcare professionals use a variety of SNA methods, leading to inconsistencies within and across organisations. Much research has explored the perspective on SNA of parents from the UK, but such research is lacking outside the UK context. Methods We conducted focus groups with Belgian parents of children 6 months to 12 years old, who were recruited through maximum variation sampling. We transcribed the interviews verbatim. Using a combination of inductive and deductive ‘in vivo’ coding we developed themes from the data. As per the Grounded Theory approach, we reiterated between data collection, coding, and analysis. After participant validation of provisional themes, we constructed the final thematic framework. Results Through six focus groups with 30 parents, we identified five themes: (1) Relevant background information; (2) To know what to expect, what to look out for; (3) Instructions on child homecare and when to revisit a physician; (4) Physicians who consider parents’ perspectives and contexts; (5) A reliable source that provides SNA only when necessary, possibly in a multimodal way. Conclusions We identified five themes from Belgian parents’ views on SNA, aligning with prior UK research. These findings form an evidence base for developing a consensus statement on the content and form of SNA supported by both parents and experts from high-income countries.